1994
DOI: 10.1126/science.8108732
|View full text |Cite
|
Sign up to set email alerts
|

Premature p34 cdc2 Activation Required for Apoptosis

Abstract: Activation of the serine-threonine kinase p34cdc2 at an inappropriate time during the cell cycle leads to cell death that resembles apoptosis. Premature activation of p34cdc2 was shown to be required for apoptosis induced by a lymphocyte granule protease. The kinase was rapidly activated and tyrosine dephosphorylated at the initiation of apoptosis. DNA fragmentation and nuclear collapse could be prevented by blocking p34cdc2 activity with excess peptide substrate, or by inactivating p34cdc2 in a temperature-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
298
0
5

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 556 publications
(329 citation statements)
references
References 22 publications
26
298
0
5
Order By: Relevance
“…Cdc25A has been reported to be both necessary and su cient for apoptosis by c-Myc (Galaktionov et al, 1996). Although this observation has not been extended, it is consistent with suggestions of a role in apoptosis in particular settings for aberrant activation of cdc2 (also a putative target gene [Born et al, 1994]) (Shi et al, 1994;Chen et al, 1995). Three other cell cycle regulators that are not genetic targets of c-Myc, Cdk2, Cdk3, and cyclin D3, have also been reported to enhance apoptosis by c-Myc (Janicke et al, 1996;Braun et al, 1998).…”
Section: Myc Target Genes and Apoptosissupporting
confidence: 69%
“…Cdc25A has been reported to be both necessary and su cient for apoptosis by c-Myc (Galaktionov et al, 1996). Although this observation has not been extended, it is consistent with suggestions of a role in apoptosis in particular settings for aberrant activation of cdc2 (also a putative target gene [Born et al, 1994]) (Shi et al, 1994;Chen et al, 1995). Three other cell cycle regulators that are not genetic targets of c-Myc, Cdk2, Cdk3, and cyclin D3, have also been reported to enhance apoptosis by c-Myc (Janicke et al, 1996;Braun et al, 1998).…”
Section: Myc Target Genes and Apoptosissupporting
confidence: 69%
“…We found here that the delay in mitotic exit was associated with apoptosis in the NIH-OVCAR-3 cell line. Several studies have indicated that p34 cdc2 activity mediates apoptotic cell death (Shi et al, 1994;Shimizu et al, 1995), and it has been suggested that p34 cdc2 plays a role in paclitaxel induced-apoptosis (Donaldson et al, 1994). In the present study, we found that a prolonged activation of p34 cdc2 in the absence of p21 expression was associated with apoptosis, whereas apoptosis did not occur when p21 was elevated enabling an earlier inhibition of p34 cdc2 activity.…”
Section: In¯uence Of Antisense-p21 On Cell Survival After Paclitaxel supporting
confidence: 57%
“…Cellular effects include inhibition of DNA synthesis and RNA transcription, which leads to the activation of cell cycle checkpoints and transient S-phase arrest followed by a durable G 2 /M arrest (Shi et al, 1994;Shapiro and Harper, 1999;Gonzalez et al, 2001;Reedijk, 2003;Siddik, 2003). In this study, we investigated the cell cycle effects of novel Titanocenes X and Y.…”
Section: Discussionmentioning
confidence: 99%